2008
DOI: 10.1155/2008/309721
|View full text |Cite
|
Sign up to set email alerts
|

Association of Single Nucleotide Polymorphisms in the IL‐18 Gene with Production of IL‐18 Protein by Mononuclear Cells from Healthy Donors

Abstract: IL-18 has proinflammatory effects and participates in both innate and adaptive cellular and humoral immunity. A number of SNPs that influence IL-18 production are found in the gene promoter region. We investigated the association of SNPs in the IL-18 promoter at −607 and −137 with the level of IL-18 protein production by PBMC from healthy donors from Southwestern Siberia. The genetic distribution of these SNPs in the promoter site was established by PCR. IL-18 protein production was determined by ELISA. Our re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 18 publications
0
17
1
Order By: Relevance
“…Results from linkage disequilibrium investigations indicate a significant association between IL-18 -137 G>C and IL-18 105 A>C polymorphic variants [34,40]. Moreover, individuals bearing the IL-18 AA genotype exhibited a higher production of this cytokine than subjects bearing either the AC or CC genotype [34].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Results from linkage disequilibrium investigations indicate a significant association between IL-18 -137 G>C and IL-18 105 A>C polymorphic variants [34,40]. Moreover, individuals bearing the IL-18 AA genotype exhibited a higher production of this cytokine than subjects bearing either the AC or CC genotype [34].…”
Section: Discussionmentioning
confidence: 96%
“…Many polymorphic variants in IL-18 promoter regions influence expression of IL-18 and may affect the blood plasma level of IL-18 [22,34,40]. It has been reported that single nucleotide polymorphisms in the IL-18 gene promoter at −607 C→A and −137 G→C alter the affinity of binding sites for CREB transcriptional factors and the H4TF-1 nuclear factor [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that IL18 promoter gene polymorphisms rs187238 and rs1946518, may influence promoter activity and IL18 production [12,16,17]. Previous studies have indicated that IL16 and IL18 are pro-inflammatory cytokines involved in the pathogenesis of diabetes [13,[18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, we can assume that homozygotes for the allele are the lowest producers of the cytokine and heterozygotes are the highest producers of the cytokine. Khripko et al (2008) Values are given as number (%)…”
Section: Discussionmentioning
confidence: 99%